Few-body problems in nuclear astrophysics - Mukhamedzhanov, A.; Alt, E.; Blokhintsev, L.; Cherubini, S.; Irgaziev, B.; Kadyrov, Alisher; Miljanic, D.; Musumarra, A.; Pellegriti, M.; Pirlepesov, F.; Rolfs, C.; Romano, S.; et al. (IOP PUBLISHING, 2005)
Few-body methods provide very useful tools to solve different problems important for nuclear astrophysics. Some of them are discussed below.